Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1073/pnas.96.26.15196
|View full text |Cite
|
Sign up to set email alerts
|

Quorum sensing controls expression of the type III secretion gene transcription and protein secretion in enterohemorrhagic and enteropathogenic Escherichia coli

Abstract: Enterohemorrhagic Escherichia coli O157:H7 and enteropathogenic E. coli cause a characteristic histopathology in intestinal cells known as attaching and effacing. The attaching and effacing lesion is encoded by the Locus of Enterocyte Effacement (LEE) pathogenicity island, which encodes a type III secretion system, the intimin intestinal colonization factor, and the translocated intimin receptor protein that is translocated from the bacterium to the host epithelial cells. Using lacZ reporter gene fusions, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
481
4
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 477 publications
(507 citation statements)
references
References 37 publications
13
481
4
6
Order By: Relevance
“…Genetic studies in enterohaemorrhagic E. coli (EHEC) and enteropathogenic E. coli revealed that LuxS controls the expression of the type-3 secretion system encoded by the locus of enterocyte effacement (LEE) pathogenicity island (Sperandio et al, 1999). This important virulence determinant is required for the formation of the characteristic Quorum sensing in bacterial virulence -a review attaching and effacing (AE) lesions caused by these pathogens (Celli et al, 2000).…”
Section: Quorum Sensing In Escherichia Coli Virulencementioning
confidence: 99%
“…Genetic studies in enterohaemorrhagic E. coli (EHEC) and enteropathogenic E. coli revealed that LuxS controls the expression of the type-3 secretion system encoded by the locus of enterocyte effacement (LEE) pathogenicity island (Sperandio et al, 1999). This important virulence determinant is required for the formation of the characteristic Quorum sensing in bacterial virulence -a review attaching and effacing (AE) lesions caused by these pathogens (Celli et al, 2000).…”
Section: Quorum Sensing In Escherichia Coli Virulencementioning
confidence: 99%
“…Subsequently, AI-2 production was verified in a large number of species and the AI-2 QS system was recognized to be involved in the regulation of a range of functions in diverse bacteria [6,7,10,[12][13][14]. In contrast to other autoinducers that are specific for a narrow range of organisms, the widely conserved AI-2 has been hypothesized to be a universal language for interspecies communication [6,9,10,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…Integration host factor (IHF) directly activates the expression of Ler (Friedberg et, al., 1999). Additional factors, including Fis, Per and a quorum sensing regulator, are also involved in the modulation of LEE1 expression (Goldberg et al, 2001;Kanamaru et al, 2000;Mellies et al, 1999;Sperandio et al, 1999Sperandio et al, , 2002a.…”
Section: Introductionmentioning
confidence: 99%